Analisis Preferensi Konsumen Terhadap Produk Beras di Pasar Baru Cikarang Kabupaten Bekasi - Adriyan, Fikri; Azzahra, Fatimah; Mahatmayana, I Ketut Manu (UNIVERSITAS LABUHANBATU, 2024)
Consumer preference for a product is based on utility and importance value. Consumers of rice in the Pasar Baru Cikarang rarely choose the attribute and levels of the rice product is the color, hygiene, type, aroma, and price. The purpose of this research is to analyze the usefulness of consumer preferences and the importance of consumer preference in choosing rice products in Pasar Baru Cikarang Kabupaten Bekasi with the time of research from May to June. The method used in this study is quantitative methods and descriptive methods. Data analysis used is conjoin analysis. Determination of respondents using accidental sampling technique, with a total of 100 respondents. The results of this study show that of the total respondents, the combination of products in choosing rice products that are useful to the preference of consumer and interests to consumer preference is color with clear white, hygiene without fleas, type of pulen, aroma of fragrance, and price of Rp10.000/kg – Rp12.000/kg. In choosing a rice product, the sequence of the most important attribute that influence consumer purchase is the first color attribute with a presentation of 45.32%, the second price atribut with a persentage of 16.61%, the third aroma attribute with a persentage of 15.61%, four hygienic atribut with a persentage of 15,52% and the last is the type attribute with a persentage of 7.34%. Keywords: conjoint analysis, rice, consumer preferences